Delightful Fruits and Bitter Weeds: Textual Consumption and Spiritual Identity in The Orcherd of Syon - Alakas, Brandon (Journal of medieval religious cultures, 2022)
Prologues at the beginning of The Orcherd of Syon, which reimagine sCatherine of Siena’s Dialogo as a garden through which readers stroll, promote a material understanding of reading rooted in a complex notion of what occurred when devout readers encountered contemplative texts. These horticultural metaphors merit careful attention because they align Birgittine meditative reading with broader approaches among female religious toward food practice, the material world, and imitatio. Drawing these discourses together, The Orcherd, this article argues, offers readers an opportunity to communicate directly with God in a way akin to visionaries and prophets.